Batgirl, year one - Beatty, Scott, 1969- (DC Comics, 2023)
"Determined to join the ranks of crime-fighters against the wishes of her police-captain father, Barbara Gordon dons a caped costume to become Batgirl, and must overcome Batman's skepticism while taking on archvillain Killer Moth."--